Zinc oxide nanoparticles prepared through microbial mediated synthesis for therapeutic applications: a possible alternative for plants - Murali, Mahadevamurthy; Gowtham, H. G.; Shilpa, N.; Singh, S. Brijesh; Aiyaz, Mohammed; Sayyed, R. Z.; Shivamallu, Chandan; Achar, Raghu Ram; Silina, Ekaterina; Stupin, Victor; Manturova, Natalia; Shati, Ali A.; et al. (Frontiers in Microbiology, 2023)
Zinc oxide nanoparticles (ZnO-NPs) synthesized through biogenic methods have gained significant attention due to their unique properties and potential applications in various biological fields. Unlike chemical and physical approaches that may lead to environmental pollution, biogenic synthesis offers a greener alternative, minimizing hazardous environmental impacts. During biogenic synthesis, metabolites present in the biotic sources (like plants and microbes) serve as bio-reductants and bio-stabilizers. Among the biotic sources, microbes have emerged as a promising option for ZnO-NPs synthesis due to their numerous advantages, such as being environmentally friendly, non-toxic, biodegradable, and biocompatible. Various microbes like bacteria, actinomycetes, fungi, and yeast can be employed to synthesize ZnO-NPs. The synthesis can occur either intracellularly, within the microbial cells, or extracellularly, using proteins, enzymes, and other biomolecules secreted by the microbes. The main key advantage of biogenic synthesis is manipulating the reaction conditions to optimize the preferred shape and size of the ZnO-NPs. This control over the synthesis process allows tailoring the NPs for specific applications in various fields, including medicine, agriculture, environmental remediation, and more. Some potential applications include drug delivery systems, antibacterial agents, bioimaging, biosensors, and nano-fertilizers for improved crop growth. While the green synthesis of ZnO-NPs through microbes offers numerous benefits, it is essential to assess their toxicological effects, a critical aspect that requires thorough investigation to ensure their safe use in various applications. Overall, the presented review highlights the mechanism of biogenic synthesis of ZnO-NPs using microbes and their exploration of potential applications while emphasizing the importance of studying their toxicological effects to ensure a viable and environmentally friendly green strategy.